Computerized Physician Order Entry (CPOE) in Reducing Medication Error: A Narrative Review - Angela, Natalya; Adisasmito, Wiku Bakti Bawono (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
Medication error leads to death and injury every day, causing lower quality of life and spend almost 1% of total global health expenditure. One of the solution of to prescribing error is using technology such as Computer Physician Order Entry (CPOE). This study purpose is to assess the use of CPOE in reducing medication error. The research method is a review of the narrative literature using systematic research, with 14 included studies. CPOE systems in hospitals were found to be capable of reducing medication errors especially in prescribing and administrative stage. However, CPOE system can be associated with new types of medication error, therefore, CPOE system must considered human factor, tailored according to the need of the hospital, and continuous training to reduce medication error.